The Prosecution in Trial In Absentia Of Money Laundering Case Resulted from Conventional Case - Rudi Pradisetia Sudirdja (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2019)
In Indonesia, the provision of in absentia in the Money Laundering Crime Law raises problems if the crime act is originally conventional crime act. Conventional crime act should be handled based on the provisions of the Indonesian Criminal Law Procedures Code. On the one hand, the Money Laundering Crime Law regulates the provisions of the court in absentia and, on the other hand, the Indonesian Criminal Law Procedures Code does not recognize trial in absentia. This study covers the issue. To be precise, it reveals the possibility of a conventional crime act that is charged with the Money Laundering Crime Law to be tried in absentia based on the principle of formal legality. In addition, it discusses the strategy of prosecution of money laundering crime act in trial in absentia for cases that are originally conventional crime act based on the principle of due process of law. This study used analytical description research specifications and the normative juridical method. The data was collected through a document study. In accordance with the approaches, the data were analyzed in qualitative-juridical manners. This study concludes several points. The first, based on the principle of legality of formal law, the implementation of trial in absentia against general criminal acts cannot be carried out. The second, based on the principle of due process of law, the prosecution strategy in trial in absentia fur such cases are that (1) the prosecution of money laundering crime and original crime must be done separately; (2) the public prosecutor must delay the transfer of original criminal acts to the court until the accused is found and presented; (3) the indictment must be prepared in a single form; (4) the indictment must draw legal facts about the original crime; and (5) the public prosecutor can prove the legal facts about the original crime in the element of ‘assets resulting from the crime’ in the money laundering offense.Strategi Penuntutan Dalam Peradilan In Absensia Terhadap Tindak Pidana Pencucian Uang Dengan Tindak Pidana Asal Konvensional AbstrakImplementasi ketentuan in absensia dalam Undang-Undang Tindak Pidana Pencucian Uang (TPPU) menimbulkan persoalan bilamana tindak pidana pencucian uang berasal dari tindak pidana umum (konvensional) yang hukum acaranya mengikuti ketentuan KUHAP. Pada satu sisi, TPPU mengatur ketentuan peradilan in absensia, pada sisi lain tindak pidana asal tidak mengenal peradilan in absensia. Studi ini difokuskan pada persoalan tersebut. Beberapa cakupan masalah dalam studi ini mencoba mengemukakan (1) apakah tindak pidana umum (konvensional) yang menjadi tindak pidana asal TPPU dapat disidangkan secara in absensia berdasarkan prinsip legalitas formal; dan (2) strategi penuntutan tindak pidana pencucian uang dalam peradilan in absensia dengan tindak pidana asal tindak pidana umum (konvensional) berdasarkan asas due process of law. Studi ini menggunakan spesifikasi penelitian deskripsi analitis. Metode pendekatan yang digunakan dalam studi ini adalah yuridis normatif. Teknik pengumpulan data melipui studi dokumen. Berdasarkan kepada metode pendekatan yang diterapkan, data yang diperoleh untuk penelitian ini dianalisis secara yuridis kualitatif. Ada beberapa simpulan yang dapat dihasilkan dari studi ini. Pertama, berdasarkan asas legalitas dalam hukum formal, implementasi peradilan in absensia terhadap tindak pidana asal tindak pidana umum (konvensional) tidak dapat dilaksanakan. Kedua, dengan berpedoman pada asas due process of law, maka strategi penuntutan in absensia dalam kondisi tersebut adalah bahwa (1) mekanisme penuntutan TPPU dan tindak pidana asal harus dilakukan secara terpisah; (2) penuntut umum harus menunda pelimpahan tindak pidana asal ke pengadilan sampai terdakwa ditemukan; (3) Surat dakwaan harus disusun dengan bentuk tunggal; (4) Dalam surat dakwaan harus tergambar fakta hukum ihwal tindak pidana asal; dan (5) Penuntut Umum dapat membuktikan fakta hukum ihwal tindak pidana asal dalam unsur “harta kekayaan hasil tindak pidana” pada delik TPPU.DOI: https://doi.org/10.22304/pjih.v6n2.a5